Causal analysis on DNA methylation reveals key regulators in aging and senescence - Cui, Tingyi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Aging is a multifaceted biological phenomenon influenced by genetic, epigenetic, and environmental factors. Cellular senescence, characterized by an irreversible cell cycle arrest, is a pivotal mechanism contributing to aging and age-related diseases. It is also associated with alterations in DNA methylation, a key epigenetic marker. However, the causal link between senescence-associated DNA methylation changes and aging outcomes remains elusive. In our study, we analyzed three distinct methods to induce cellular senescence and systematically evaluated the resultant DNA methylation profiles. Utilizing Mendelian Randomization, we identified that 4.1% of the methylated loci were significantly associated with aging outcomes and accounted for the majority of the observed variance. Further mediation analysis pinpointed key genes, including CISD2, MARS2, and ETFB, that serve as mediators for these epigenetic effects. Experimental validation using Senescence-Associated-β-Galactosidase (SA-β-gal) staining confirmed that knockdown of these genes triggers cellular senescence. Our findings provide compelling evidence for the causal role of DNA methylation in cellular senescence and its impact on aging.